An aggressive cabergoline-resistant, temozolomide-responsive macroprolactinoma due to a germline SDHB pathogenic variant in the absence of paraganglioma or pheochromocytoma - Alzahrani, Ali S.; Bin Nafisah, Abdulghani; Alswailem, Meshael; Moria, Yosra; Poprawski, Dagmara; Al-Hindi, Hindi; Pacak, Karel (Frontiers in Endocrinology, 2023)
Context: Germline succinate dehydrogenase subunit B (SDHB) pathogenic variants are characteristic of familial paraganglioma (PGL) syndrome type 4. This syndrome frequently presents with abdominal PGL and has high tendency for locally aggressive behavior and distant metastasis. The vast majority of pituitary adenomas (PAs) are sporadic. However, PAs can be part of a number of familial tumor syndromes such as multiple endocrine neoplasia type 1 (MEN 1) or more rarely in association with pheochromocytoma and PGL (referred to as 3P syndrome). Only a limited number of PAs in association with SDHB-related PGL has been reported and the vast majority occurred subsequently or simultaneously with pheochromocytoma/PGL (collectively abbreviated as PPGL). In this report, we describe a young patient who had a giant pituitary macroprolactinoma resistant to large doses of cabergoline (CBG) and external beam radiotherapy (XRT). The patient did not have personal history of PPGL but was found to carry a germline SDHB pathogenic variant.Case report: A 38-year-old woman presented with headache, visual disturbances and galactorrhea and was found to have a 34 mm macroprolactinoma. She was treated with CBG 3-4 mg per week but PA continued to grow and caused significant cranial pressure symptoms. She underwent two transsphenoidal surgeries with rapid tumor recurrence after each one. She received XRT but PA continued to grow. She was finally treated with temozolomide with excellent response. Whole exome and subsequent Sanger sequencing confirmed that she has a pathogenic monoallelic SDHB mutation (NM_003000:c.C343T, p.R115*). PA tissue showed loss of heterozygosity for the same mutation and absent SDHB immunostaining confirming the pathogenic role of this SDHB mutation.Conclusion: Germline SDHB mutations can rarely cause PA in the absence of PPGL. They should be considered as a possible cause of aggressiveness and resistance to dopamine agonists in similar cases.